The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/txd.0000000000001253
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Hepatitis D Virus in the United States: A UNOS Study on Outcomes in the MELD Era

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…Multiple prior studies have showed an increased morbidity and mortality associated with chronic hepatitis D virus infection 2–4 . We similarly noticed a statistically significant increase in need for liver transplantation among the HDV+ group.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Multiple prior studies have showed an increased morbidity and mortality associated with chronic hepatitis D virus infection 2–4 . We similarly noticed a statistically significant increase in need for liver transplantation among the HDV+ group.…”
Section: Discussionsupporting
confidence: 76%
“…This infection can either be concurrent coinfection with HBV or superinfection in a patient with chronic hepatitis B (CHB) 1 . Chronic HDV infection is the most severe form of chronic viral hepatitis and is associated with increased progression to liver cirrhosis, hepatocellular carcinoma (HCC), mortality from liver failure, and the need for liver transplant (LT) 2–4 . Despite its discovery almost 45 years ago in 1977 by Rizzetto et al, 5 the global burden of HDV infection remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Because of the accelerated clinical course, patients with HDV cirrhosis are younger than HBV and HCV cirrhotics and run faster into decompensation 10 ; death is usually caused by liver failure rather than hepatocellular carcinoma (HCC), which may have no time to develop for the rapid progression of HDV disease. These clinical features were confirmed in a recent report of 152 HDV transplants performed in the United States in the years 2002–2019 11 ; the patients were younger than HBV transplants, often coinfected with the HCV, and likely to be listed for decompensated liver disease rather than for HCC.…”
Section: Introductionsupporting
confidence: 59%
“…54 The disproportionate number of HDV to HBV LTs against the minimal epidemiologic burden of HDV in Europe presumably results from the use of HBV antivirals that have afforded effective control of chronic hepatitis B, in contrast to the poor efficacy of interferon therapy used for CHD, which could not prevent progression of the disease to end-stage cirrhosis. In analogy with the American experience, 11 in Turin in the last decade, 62.3% of the HDV patients were transplanted for liver failure and 37.7% for HCC, whereas only 29.5% of the HBV patients were transplanted for liver failure and 70.5% for HCC, the development of which could not be prevented by antiviral therapy (Table 2).…”
Section: The Futurementioning
confidence: 98%